Accumulation of Some Heavy Metals in Flavoparmelia caperata and Usnea dasypoga As Air Quality Bioindicator in Palembang City - Mirawati Mirawati; Arinafril Arinafril; M. Fasisal (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2018)
Flavoparmelia caperata and Usnea dasypoga lichen for the first time was used to assess the concentration of heavy metals in the air in Palembang City. 5 heavy metals Cd, Cu, Pb, Fe, and Zn were measured using the transplant method. Both samples of lichen were collected from Gununghalu, Bandung. The lichen was transplanted at 7 points on the roadside, after 8 weeks, samples were collected and analyzed using SSA. The concentration of heavy metals accumulated in F. caperata was Fe> Cu> Zn> Pb> Cd, on U. dasypoga was Fe> Zn> Cu> Pb> Cd. The results showed that both types of lichen were very suitable to be used as an air quality bioindicator. The EC ratio of both transplanted samples showed higher levels of accumulation in U. dasypoga with a significant accumulation rate on Pb metal followed by Cu, Cd, Zn, and Fe. Furthermore, dendrogram showed clustering based on the concentrations of heavy metals accumulated at each station due to differences in density and vehicle type. This indicated that the metals have the same source which derived from emissions of motor vehicles, road construction activities, and other local anthropogenic activities.